First Results on Moss Biomonitoring of Trace Elements in the Central Part of Georgia, Caucasus - Omari Chaligava; Igor Nikolaev; Khetag Khetagurov; Yulia Lavrinenko; Anvar Bazaev; Marina Frontasyeva; Konstantin Vergel; Dmitry Grozdov (Atmosphere, 2021)
The moss biomonitoring technique was used for assessment of air pollution in the central part of Georgia, Caucasus, in the framework of the UNECE ICP Vegetation. A total of 35 major and trace elements were determined by two complementary analytical techniques, epithermal neutron activation analysis (Na, Mg, Al, Cl, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Se, B, Rb, Sr, Zr, Mo, Sb, I, Cs, Ba, La, Ce, Nd, Sm, Eu, Tb, Yb, Hf, Ta, W, Th, and U) and atomic absorption spectrometry (Cu, Cd, and Pb) in the moss samples collected in 2019. Principal Component Analyses was applied to show the association between the elements in the study area. Four factors were determined, of which two are of geogenic origin (Factor 1 including Na, Al, Sc, Ti, V, Cr, Fe, Co, Ni, Th, and U and Factor 3 with As, Sb, and W), mixed geogenic–anthropogenic (Factor 2 with Cl, K, Zn, Se, Br, I, and Cu) and anthropogenic (Factor 4 comprising Ca, Cd, Pb, and Br). Geographic information system (GIS) technologies were used to construct distributions maps of factor scores over the investigated territory. Comparison of the median values with the analogous data of moss biomonitoring in countries with similar climatic conditions was carried out.